Ionic pyridinium-oxazole dyads: design, synthesis, and application in mitochondrial imaging - Shaikh, Aslam C.; Varma, Mokshada E.; Mule, Ravindra D.; Banerjee, Somsuvra; Kulkarni, Prasad P.; Patil, Nitin T. (Journal of Organic Chemistry, 2019)
We recently developed an oxidative intramolecular 1,2-amino-oxygenation reaction, combining gold(I)/gold(III) catalysis, for accessing structurally unique ionic pyridinium-oxazole dyads (PODs) with tunable emission wavelengths. On further investigation, these fluorophores turned out to be potential biomarkers; in particular, the one containing -NMe2 functionality (NMe2-POD) was highly selective for mitochondrial imaging. Of note, because of mitochondria's involvement in early-stage apoptosis and degenerative conditions, tracking the dynamics of mitochondrial morphology with such imaging technology has attracted much interest. Along this line, we wanted to build a library of such PODs which are potential mitochondria trackers. However, Au/Selecfluor, our first-generation catalyst system, suffers from undesired fluorination of electronically rich PODs resulting in an inseparable mixture (1:1) of the PODs and their fluorinated derivatives. In our attempt to search for a better alternative to circumvent this issue, we developed a second-generation approach for the synthesis of PODs by employing Cu(II)/PhI(OAC)(2)-mediated oxidative 1,2-amino-oxygenation of alkynes. Thes newly synthesized PODs exhibit tunable emissions as well as excellent quantum efficiency up to 0.96. Further, this powerful process gives rapid access to a library of NMe2-PODs which are potential mitochondrial imaging agents. Out of the library, the randomly chosen POD-3g was studied for cell-imaging experiments which showed high mitochondrial specificity, superior photostability, and appreciable tolerance to microenvironment changes with respect to commercially available MitoTracker green.

`Turning on' to glutathione: a rhodamine-based fluorescent chemodosimeter with nanomolar sensitivity - Badekar, Pooja S.; Deo, Harshada S.; Varma, Mokshada E.; Kulkarni, Prasad P.; Maibam, Ashakiran; Krishnamurty, Sailaja; Kumbhar, Anupa A. (ChemistrySelect, 2024)
A new colorimetric and fluorescence turn-on chemodosimeter for selective detection of GSH over Cys and Hcy with 34-fold enhancement in emission intensity is reported. Probe 1 exhibited ultra-sensitivity toward GSH with 0.125 nM detection limit and successfully displayed GSH detection in MCF-7 live cells. The mechanism of sensing is established by density functional theoretical calculations.
Keywords: Chemodosimeter; Fluorescence turn-on; GSH; MCF-7 cells; Rhodamine